Resisting Representation. - Scarry, Elaine (Oxford University Press, 1994)
Renowned scholar Elaine Scarry's book, The Body in Pain, has been called by Susan Sontag "extraordinary ... large-spirited, heroically truthful." The Los Angeles Times called it "brilliant, ambitious, and controversial." Now Oxford has collected some of Scarry's most provocative writing. This collection of essays deals with the complicated problems of representation in diverse literary and cultural genres--from her beloved sixth-century philosopher Boethius, through the nineteenth-century novel, to twentieth-century advertising. qWe often assume that all areas of experience are equally available.